CAPACITY DEVELOPMENT APPROACHES FOR CHIEFS AND LOCAL GOVERNMENT AUTHORITIES IN GHANA: THE CASE OF THE ROYAL ACADAMY - Boateng, K.; Afranie, S. (UDS International Journal of Development, 2021)
Chiefs and local government authorities are instrumental in community development. However, the branding of chieftaincy by the post-colonial government as anachronistic and undemocratic and the removal of chieffs from local government structures to curtail their powers affected their chances to be abreast with the dynamics of modern development concepts and approaches. Though currently the chieftaincy institution boasts of educated elites, some are not conversant with laws and policies on local government. Language barrier is a challenge in some cases for collaboration between the two actors as some Assembly officials speak languages that are different from the local languages of communities in which they work. Additionally, local government authorities have been criticised for their low capacity level and their contributions to development is questioned. The study adopted qualitative approaches to examine capacity development approaches within chieftaincy and local government systems. Nineteen participants including chiefs, members of District Assemblies, key informants and local government officials were sampled through purposive and convienent sampling techniques. The study unearthed that majority of the participants were unaware about the Royal Acadamy, a capacity development facility for chiefs. Challenges affecting capacity development included lack of funds, change in government, traditional practices and customs, and elitism in chieftaincy. The paper concludes that capacity development can facilitate community development, and minimise conflict between chiefs and local government authorities. The paper recommends that the Ministry of Chieftaincy and Religious Affairs take steps to operationalise the commencement of activities of the Royal Acadamy.